KiDS-i-800: comparing weak gravitational lensing measurements from same-sky surveys. Issue 4 (5th April 2018) - Amon, A; Heymans, C; Klaes, D; Erben, T; Blake, C; Hildebrandt, H; Hoekstra, H; Kuijken, K; Miller, L; Morrison, C B; Choi, A; de Jong, J T A; et al.
Abstract: We present a weak gravitational lensing analysis of 815 deg 2 of i -band imaging from the Kilo-Degree Survey (KiDS- i -800). In contrast to the deep r -band observations, which take priority during excellent seeing conditions and form the primary KiDS data set (KiDS‐ r ‐450), the complementary yet shallower KiDS- i -800 spans a wide range of observing conditions. The overlapping KiDS- i -800 and KiDS‐ r ‐450 imaging therefore provides a unique opportunity to assess the robustness of weak lensing measurements. In our analysis we introduce two new 'null' tests. The 'nulled' two-point shear correlation function uses a matched catalogue to show that the calibrated KiDS- i -800 and KiDS‐ r ‐450 shear measurements agree at the level of 1 ± 4 per cent. We use five galaxy lens samples to determine a 'nulled' galaxy–galaxy lensing signal from the full KiDS- i -800 and KiDS‐ r ‐450 surveys and find that the measurements agree to 7 ± 5 per cent when the KiDS- i -800 source redshift distribution is calibrated using either spectroscopic redshifts, or the 30-band photometric redshifts from the COSMOS survey.